If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (11r + 8)(3r + -4) = 0 Reorder the terms: (8 + 11r)(3r + -4) = 0 Reorder the terms: (8 + 11r)(-4 + 3r) = 0 Multiply (8 + 11r) * (-4 + 3r) (8(-4 + 3r) + 11r * (-4 + 3r)) = 0 ((-4 * 8 + 3r * 8) + 11r * (-4 + 3r)) = 0 ((-32 + 24r) + 11r * (-4 + 3r)) = 0 (-32 + 24r + (-4 * 11r + 3r * 11r)) = 0 (-32 + 24r + (-44r + 33r2)) = 0 Combine like terms: 24r + -44r = -20r (-32 + -20r + 33r2) = 0 Solving -32 + -20r + 33r2 = 0 Solving for variable 'r'. Factor a trinomial. (-8 + -11r)(4 + -3r) = 0Subproblem 1
Set the factor '(-8 + -11r)' equal to zero and attempt to solve: Simplifying -8 + -11r = 0 Solving -8 + -11r = 0 Move all terms containing r to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -11r = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -11r = 0 + 8 -11r = 0 + 8 Combine like terms: 0 + 8 = 8 -11r = 8 Divide each side by '-11'. r = -0.7272727273 Simplifying r = -0.7272727273Subproblem 2
Set the factor '(4 + -3r)' equal to zero and attempt to solve: Simplifying 4 + -3r = 0 Solving 4 + -3r = 0 Move all terms containing r to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -3r = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -3r = 0 + -4 -3r = 0 + -4 Combine like terms: 0 + -4 = -4 -3r = -4 Divide each side by '-3'. r = 1.333333333 Simplifying r = 1.333333333Solution
r = {-0.7272727273, 1.333333333}
| X^2-15=6x-11 | | x^2-12+8=0 | | X^2+16-10=0 | | 2w-5=5w+25 | | v-8+5=2 | | 3/4x=-3/8 | | -3x=-6-5x | | 8k+6=10k-2 | | 5+5x=-55-3x+3x | | 15x-12y=7 | | 3x^2+20x-28=0 | | 3(x-20)=-9 | | https://content.thinkthroughmath.com/uploads/image/image/301092/G34L315Q22064S-1affa0d9458b24f4562416b559636d53.png | | 18=y-10 | | f(x)=(x+16)(2x+16) | | 7-4x+x=-6x+13+3x | | 8x-23=4x+17 | | 4x+7=-41-12x | | 6x(x^2-9)=0 | | -15+6=m-8 | | (2^5/2)-(2^3/2) | | 1024=x^2+48x | | x+x(5)=45 | | x+x(5)= | | 9+4=5-x | | H=16t^2+75t | | 8-(2n-7)=4-3n | | 6x+12=-5x-19 | | 6x+12=6x-19 | | 9x^2-30x+25-4x^2-4x-1=24 | | 3x+5=-5x-12 | | 10t+5=-5 |